IMPLEMENTASI PENYALURAN PROGRAM BANTUAN PANGAN NON-TUNAI PADA MASYARAKAT DESA GUNUNG MASIGIT - Sulastri, Ema; Solihin, Dadin (Jurnal Pelita Nusa, 2025)
The Non-Cash Food Assistance Program (BPNT) is one of the government's efforts to increase food security and reduce the burden of expenditure on the poor. However, the effectiveness of the implementation of this program often faces obstacles, especially related to the accuracy of the target and the timeliness of distribution. This study aims to analyze the implementation of BPNT distribution in Gunung Masgitit Village, Cipatat District, West Bandung Regency. The research method used is qualitative with data collection techniques through interviews, observations, and documentation. The results of the study show that the BPNT program is quite effective in terms of good public understanding, reduced expenditure burden, and real benefits felt by Beneficiary Families (KPM). However, problems were found in the accuracy of the target due to suboptimal data updates and delays in the distribution of aid. The conclusion of this study emphasizes the need to increase socialization to program implementers, improve distribution infrastructure, and strengthen supervision so that the BPNT program can be more targeted and on time.